Cartographic storytelling: reflecting on maps through an ethnographic application in Siberia - Gertrude Saxinger (Department of Political Science, Faculty of Social Sciences, University of Vienna); Alexis Sancho Reinoso (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Sigrid Irene Wentzel (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna) (Fennia - International Journal of Geography, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:1764437 The abstract is available here: https://uscholar.univie.ac.at/o:1764437